1983
DOI: 10.1002/chin.198336209
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ANIONIC (3 + 2)‐CYCLOADDITION OF DITHIOBENZOATE ANION WITH ACTIVATED MULTIPLE BONDS

Abstract: Das Dithiobenzoat‐Anion in Form des Salzes (I) reagiert mit den aktivierten Alkinen (II) bzw. (IV) in einer 3 + 2‐Cycloadditionsreaktion zu den 1,3‐Dithiolen (III) bzw. (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…1 The reactions of the 1,3-anionic cycloaddition are typical on condition that the central Catom of -R-CS 2¯ has aromatic or heteroaromatic substituents R supporting the anion stabilization. 9,10 Thus, the salts of pyrrole-1-, thiophene-2-, furane-2-, and naphthalene-1-dithiocarboxylic acids selectively react with the dimethyl ester of acetylenedicarboxylic acid to form cycloadducts. 9 We found that the reaction of potassium pyrrole-1-carbodithioate (1) with the ethyl ester of propiolic acid (7a) and with benzoylacetylene (7b) in DMSO (room temperature, 2 hours) leads to normal adducts; the S-ethenylpyrrole-1-carbodithioates 8a, 8b in 10% and 18% yield, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…1 The reactions of the 1,3-anionic cycloaddition are typical on condition that the central Catom of -R-CS 2¯ has aromatic or heteroaromatic substituents R supporting the anion stabilization. 9,10 Thus, the salts of pyrrole-1-, thiophene-2-, furane-2-, and naphthalene-1-dithiocarboxylic acids selectively react with the dimethyl ester of acetylenedicarboxylic acid to form cycloadducts. 9 We found that the reaction of potassium pyrrole-1-carbodithioate (1) with the ethyl ester of propiolic acid (7a) and with benzoylacetylene (7b) in DMSO (room temperature, 2 hours) leads to normal adducts; the S-ethenylpyrrole-1-carbodithioates 8a, 8b in 10% and 18% yield, respectively.…”
Section: Methodsmentioning
confidence: 99%